PERFORMANCE OF ASPHALT CONCRETE CONTAINING CRUSHED AND UNCRUSHED GRAVEL WITH HIGH FLAT-PARTICLE CONTENT - Muhammad Ahlan; Muhammad Isya; Noer Fadhly (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2019)
The aggregate shapes affect corresponding asphalt concrete performance. Asphalt concrete composed of more cubical, angular, and coarse-textured aggregates has higher performance than the one composed of elongated, flat, rounded, and smooth aggregates. Nevertheless, the available materials might be not perfect, for example, the materials might be the gravel with high flat-particle content. These gravels commonly are crushed to form angular and coarse-textured particles; however, the post-crushing products might be flatter, although the shapes become angular and coarse. No research has been found that compares the performance of asphalt concrete containing such aggregates. The objective of this study is to compare the performance of asphalt concrete containing high flat-particle content crushed gravel and the one containing high flat-particle content uncrushed gravel, in term of Marshall stability and Marshall durability. The Marshall method was used, in which, a total of 27 samples of asphalt concrete were tested. The result shows that the stability of asphalt concrete composed of crushed gravel with high flat-particle content is 38.8% better than the one composed of uncrushed gravel with high flat-particle content. In addition, the durability of the asphalt concrete composed of the crushed aggregate is 5.6% better than the one composed of the uncrushed aggregate. Bentuk agregat mempengaruhi kinerja beton aspal. Beton aspal yang mengandung agregat yang menyerupai kubus, bersudut, dan bertekstur kasar memiliki kinerja lebih baik dibandingkan dengan beton aspal yang mengandung agregat yang relatif bulat, lonjong, pipih, dan bertekstur licin. Namun, agregat yang tersedia tidak selalu sempurna. Material yang tersedia terkadang dapat berupa kerikil dengan kandungan agregat pipih yang tinggi. Kerikil ini biasanya dipecah untuk menjadi agregat yang bersudut dan bertekstur kasar, namun setelah dipecah agregat dapat lebih pipih walaupun bentuknya bersudut dan teksturnya kasar. Sejauh ini, belum ditemukan penelitian yang membandingkan kinerja beton aspal yang mengandung kerikil dengan kandungan agregat pipih yang tinggi pada saat agregat belum dan sudah dipecah. Tujuan dari penelitian ini adalah membandingkan beton aspal yang mengandung kerikil yang dipecah dengan kepipihan yang tinggi dan beton aspal yang mengandung kerikil yang tidak dipecah juga dengan kandungan agregat pipih yang tinggi, dalam hal stabilitas dan durabilitas Marshall. Metode yang digunakan adalah Metode Marshall. Pada metode ini, total 27 benda uji dites. Hasil penelitian menunjukkan stabilitas beton aspal yang mengandung agregat yang dipecah adalah 38.8% lebih baik dibandingkan dengan beton aspal yang mengandung agregat yang tidak dipecah. Begitu juga, durabilitas beton aspal yang mengandung agregat yang dipecah 5.6% lebih baik daripada beton aspal yang mengandung agregat yang tidak dipecah.